News virality in disaster communication: An encoding–decoding study of community reception in Sumber Mujur, Mount Semeru - Radius Setiyawan; Agus Budiman; Holy Ichda Wahyuni (Universitas Ahmad Dahlan, 2026)
This study examines how local communities interpret news about the Mount Semeru eruption on social media. It argues that disaster news constructs meaning through language, visuals, and framing, rather than merely conveying facts. Media portrayals often dramatize disasters, creating a gap between media representations and local experiences. While existing studies tend to focus on media production or textual analysis, this research positions affected communities as active agents in meaning-making. In doing so, it addresses the limited scholarship on community-based disaster reception in Indonesia. Using a qualitative approach, in-depth interviews were conducted with residents of Sumber Mujur Village, Candipuro District, Lumajang Regency, East Java, following the eruption (January–February 2022). The analysis is guided by Stuart Hall’s encoding–decoding framework to explore how communities interpret and respond to disaster news. The findings identify three decoding positions. First, a negotiated reading of the “Rumini died beside her mother” report, where the event is accepted but the emotional framing is questioned. Second, a dominant-hegemonic reading of the “house intact from the eruption” report, interpreted through religious values as a symbol of hope despite its simplification of the disaster. Third, an oppositional reading of the “Semeru lava can cause a tsunami” report, which is rejected as hyperbolic, geographically inaccurate, and potentially panic-inducing. This study demonstrates that community reception is not passive but actively negotiates media meaning within local socio-cultural contexts. It extends encoding–decoding theory by grounding it in disaster communication at the community level in Indonesia, and highlights the importance of context-sensitive, non-exaggerative, and victim-centered reporting.